Case report: Primary osteomyelitis of the sternum in a seven-month-old male - Anthony Tran, M.D., M.S; Tariq Lescouflair, M.D; Shrey Patel, M.D; Richard Weiss, M.D (Elsevier, 2017)
Primary sternal osteomyelitis (PSO) in the pediatric population is a rare infection with potentially catastrophic ramifications. We describe a case in a seven-month-old male patient who presented without evidence of trauma or a source of infection. Open sternal biopsies and cultures revealed Methicillin Sensitive Staphylococcus Aureus (MSSA) as the organism. We discuss the preoperative and surgical management of this patient as well as the antibiotic treatment strategy.